Hubungan Antara Stres Akademik Dengan Perilaku Merokok Pada Mahasiswa - Rahmadianti, Anisa; Leonardi, Tino (Jurnal Syntax Fusion, 2023)
This research is based on the phenomenon of smoking behavior among college students in Indonesia. One of the factors that influence student behavior is academic stress. Academic stress is a condition where students are unable to carry out academic demands. This study aims to determine the relationship between academic stress and smoking behavior in college students. This study uses a correlational quantitative method. The sampling technique used was non-probability purposive sampling. The respondents of this study were 101 students at several universities in Indonesia. The measurement tools used are the Student-life Stress Inventory and Glover-Nillson Smoking Behavior. Data analysis was performed using the Pearson Product-Moment method with the help of SPSS version 25 software. The results revealed that academic stress had a significant positive relationship to smoking behavior (p <.05; r = 0.501). The conclusion from this study the higher the level of academic stress, the higher the smoking behavior